Comparison of Serum Albumin Level in Stable & Hospitalized Patients of Chronic Obstructive Pulmonary Diseases (COPD) - Abdul Salam, Ishfaq Ahmed, Syed Amanullah Shah, Shirjeel Husain, Madiha Shah, Zeeshan Ul Haque (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was conducted to estimate the serum albumin levels in stable & hospitalized patients of COPD. Study Design: Comparative Cross Sectional Place and Duration of Study: This study was jointly carried out at of Pulmonology at Shaikh Zyed Hospital Rahim Yar Khan, Fatima Jinnah Institute of Chest Medicine Quetta and Liaquat University of medical and health sciences, Jamshoro from 1st January 2021 to December 2021. Methodology: A total of 180 cases of COPD were selected and divided into two groups; group A contained 95 cases of COPD as stable cases, and group B included 85 cases as hospitalized cases of COPD with the mentioned inclusion and exclusion criteria. The serum albumin level was estimated by the bromocresol green (BCG) method. The serum albumin level of less than 3.2 g/dl is considered hypoalbumienimia. The statistical data was analysed by SPSS version 22 by applying an independent student T test. Results: The mean serum albumin level in stable cases of COPD was 3.0 ± 0.41 g/dl while in hospitalized patients it was 2.6 ± 0.34 g/dl. The serum albumin level was statistically(P <0.001) declined in hospitalized patients of COPD as compared with stable cases of COPD. Conclusion:This study concluded that serum albumin level declined in the patients of COPD and the severity of COPD directly proportional with reduction of serum albumin level Keywords: COPD, Serum Albumin, Oxidative Stress, Inflammatory mediators